Invasive Nattrassia mangiferae infections: case report, literature review, and therapeutic and taxonomic appraisal. - Sigler, L (1997)
We report on a case of subcutaneous infection of the arm caused by the coelomycetous fungus Nattrassia mangiferae (formerly Hendersonula toruloidea) in a steroid-dependent diabetic man with chronic obstructive lung disease. The man was a resident of Arizona, where the fungus is known to be endemic on Eucalyptus camaldulensis and on citrus trees. Diagnosis of fungal infection was made by observation of narrow hyphal filaments by histopathology of biopsy specimens and isolation of a fast-growing black mold which demonstrated hyphae and arthroconidia of varying widths typical of the Scytalidium synanamorph (S. dimidiatum). The formation of pycnidia, which at maturity expressed conidia with a central median dark band, allowed for the confirmation of the isolate as N. mangiferae. Remission of the lesions occurred following intravenous therapy with amphotericin B, followed by topical clotrimazole treatment. We use this patient's case report as an opportunity to review the literature on cases of deep infection caused by Scytalidium species, to evaluate the antifungal susceptibilities of a spectrum of Scytalidium isolates, and to review the taxonomy of Scytalidium species isolated from human infections.